Islamic Education Thought According to Syafaruddin - Armansyah Armansyah; Usiono Usiono; Azizah Hanum OK (Edumaspul: Jurnal Pendidikan, 2024)
Currently, Islamic education ideas are not only conveyed by Muslims but also by people of other religions. Therefore, there is a need for Islamic educational thinking that should be produced by Muslims themselves, so that the results of their thinking are correct and in line with Islamic principles and sharia. Therefore, this scientific study aims to examine in more depth the thoughts on Islamic education according to the perspective of Prof. Dr. Syafaruddin, M.Pd. This scientific study uses the Systematic Literature Review (SLR) method with PRISMA analysis. The results of the analysis state that in his perspective, Prof. Dr. Syafaruddin, M.Pd. not only views Islamic education as teaching related to Islamic values, but more than that. He views Islamic education as a complex system, in which structured management actions are needed to be able to maintain and develop Islamic education amidst the onslaught of current developments